2016
DOI: 10.1063/1.4959812
|View full text |Cite
|
Sign up to set email alerts
|

Anomalous pinch of turbulent plasmas driven by the magnetic-drift-induced Lorentz force through the Stokes-Einstein relation

Abstract: It is found that the Lorentz force generated by the magnetic drift drives a generic plasma pinch fluxes of particle, energy and momentum through the Stokes-Einstein relation. The proposed theoretical model applies for both electrons and ions, trapped particles and passing particles.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…as shown in figures 6(a1) and (a2). It has been proven that equation ( 15) also works at the nonlinear stage [26]. It is found that D rr and D rK at the nonlinear stage roughly satisfy equation ( 15), as shown in figures 6(b1) and (b2).…”
Section: The Relation Between D Rr and D Rkmentioning
confidence: 74%
See 1 more Smart Citation
“…as shown in figures 6(a1) and (a2). It has been proven that equation ( 15) also works at the nonlinear stage [26]. It is found that D rr and D rK at the nonlinear stage roughly satisfy equation ( 15), as shown in figures 6(b1) and (b2).…”
Section: The Relation Between D Rr and D Rkmentioning
confidence: 74%
“…It can be seen from figure 6 that D rK is mainly contributed by trapped particles and, in the trapping cone, the D rK directly obtained by NDTM is close to that obtained using equation (15), which indicates equation ( 15) is well satisfied; meanwhile, out of the trapping cone, especially in the velocity space of v ⊥ < v T outside of the resonance curve, a difference is found between D rK obtained by the above two methods, which indicates equation ( 15) is not well satisfied. The reasons for the difference are as follows: (1) note that in obtaining equation ( 15) [26], the cos θ ≈ 1 was used by invoking the strong ballooning approximation; when the strong ballooning approximation is not well satisfied, cos θ ≈ 1 is still a good approximation for trapped particles, but not a good one for passing particles; (2) the coefficient,…”
Section: The Relation Between D Rr and D Rkmentioning
confidence: 99%
“…After calculating the necessary deviations of F 0 and substituting them into equation (3), we obtain 3,4,5. In order to conveniently analyze the transport coefficients and fluxes in section 4, analogous to the treatment in [21], we have defined a set of driving forces…”
Section: Dispersion Relationmentioning
confidence: 99%
“…To end this subsection, we point out that if one does not absorb the contribution from the driven source in the velocity space into those in the spatial space, then one should add another term in equation (73b) to reflect this contribution; obviously, this term will explicitly appear in equation (84). Note that this term will also appear, for example, in equation (85) as a heating source [51]. Equation ( 86) is obtained by substituting equation (85) into equation (84), one can easily deduce that the form of equation ( 86) is kept unchanged.…”
Section: The Zonal Radial Electric Field In the Cylindrical Geometrymentioning
confidence: 99%